Crime culture : figuring criminality in fiction and film - Nicol, Bran, 1969-; McNulty, Eugene; Pulham, Patricia, 1959- (Continuum literary studies., 2011)
Exploring crime in works which are not usually associated with crime genres, this work breathes new life into staple themes in crime fiction/cinema such as gender, the body and the city, and offers analyses of new elements such as the mythology of the hitman and the cultural impact of 'senseless' murders.